1981
DOI: 10.1002/ajp.1350010208
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal human spermatozoa including comparative data from apes

Abstract: Several reports have shown that the sperm counts in man have declined over the last 20 years. Human spermatozoa also exhibit a structural and chemical variation that is greater than that of most other mammals. Human fecundability is low compared with other examined animal species. Possible causes of these three classes of findings are analyzed: The effect of clothing or of other undue heating of the scrotum; xenobiotic influences such as smoking, lead compounds, X-rays, alkylating agents; degeneration effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…5). The mean per cent of sperm with abnormal forms remained slightly above baseline values at 18 months post-treatment, although the actual values (28-35%) are within the normal range for men (Afzelius, 1981;Schwartz et al, 1984).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…5). The mean per cent of sperm with abnormal forms remained slightly above baseline values at 18 months post-treatment, although the actual values (28-35%) are within the normal range for men (Afzelius, 1981;Schwartz et al, 1984).…”
Section: Discussionmentioning
confidence: 75%
“…Such a decrease in motility could result from alteration of sperm motility during transit through the cauda epididymis, which is known to be thermo-dependent in animals (Foldesy & Bedford, 1982). Another cause could be a structural abnormality of the sperm tail, linked to impairment of sperm differentiation within the seminiferous tubules, as evidenced by the increased rate of abnormally shaped sperm (Afzelius, 1981). Scanning electron microscopy could help to resolve this question.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few examples of species that have large numbers of morphologically abnormal spermatozoa and propagate effectively, including cheetahs (Wildt et al, 1983) and primates such as humans and gorillas (Afzelius, 1981). However, the great majority of animal species studied Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of morphological abnormalities differentiates human sperm from that of other species (MacLeod -1964). It has been suggested that this difference might be related to environmental factors and/or to people's habits (Afzelius -1981). It has been possible, for example, to induce morphologic abnormalities in the mouse by using different chemical agents (Wyrobek and Bruce -1975).…”
Section: Introductionmentioning
confidence: 99%